Assessment of Reading and Writing in English Learning for First-Grade Elementary School - apriliyan, regy ahmad (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2024)
Abstract This study aims to explore and describe the assessment methods used to evaluate the reading and writing abilities of first-grade elementary school students in English. The research design adopts a descriptive qualitative approach to gather in-depth, non-numerical data that can provide rich insights into the assessment process. The sample consists of first-grade elementary school students who are learning English, with careful consideration given to selecting a diverse sample representing various socioeconomic backgrounds and language proficiency levels. This approach ensures a comprehensive understanding of the assessment methods and their applicability across different student populations. Data collection involves developing assessment instruments that align with grade 1 English learning objectives, focusing specifically on reading and writing components. These instruments are designed to be suitable for the students' developmental level, taking into account their limited vocabulary and literacy skills. Examples of assessment instruments used include open-ended reading comprehension tasks, picture-based writing prompts, and observation of students' writing behaviors. Through this study, valuable insights into the effective assessment methods for evaluating the reading and writing abilities of first-grade elementary school students in English learning are expected to be gained. The findings of this research can inform instructional practices, curriculum development, and assessment strategies to support students' language acquisition and proficiency at this critical stage of their education. The descriptive qualitative method allows for a detailed exploration and description of the assessment methods employed, providing a deeper understanding of their effectiveness and potential areas for improvement.